What Is the Critical Value of Glenoid Bone Loss at Which Soft Tissue Bankart Repair Does Not Restore Glenohumeral Translation, Restricts Range of Motion, and Leads to Abnormal Humeral Head Position?. (November 2016) - Shin, Sang-Jin; Koh, Yong Won; Bui, Christopher; Jeong, Woong Kyo; Akeda, Masaki; Cho, Nam Su; McGarry, Michelle H.; Lee, Thay Q.
Background: A general consensus has been formed that glenoid bone loss greater than 20% to 25% is the critical amount at which bony augmentation procedures are needed; however, recent clinical results suggest that the critical levels must be reconsidered to lower values. Purpose: This study aimed to find the critical value of anterior glenoid bone loss when a soft tissue repair is not adequate to restore anterior-inferior glenohumeral translation, rotational range of motion, or humeral head position using a biomechanical anterior shoulder instability model. Study Design: Controlled laboratory study. Methods: Eight cadaveric shoulders were tested with a customized shoulder testing system. Range of motion, translation, and humeral head position were measured at 60° of glenohumeral abduction in the scapular plane under a total of 40-N rotator cuff muscle loading in the following 11 conditions: intact; soft tissue Bankart lesion and repair; Bankart lesion with 10%, 15%, 20%, and 25% glenoid bone defects based on the largest anteroposterior width of the glenoid; and soft tissue Bankart repair for each respective glenoid defect. Serial osteotomies for each percentage of bone loss were made parallel to the long axis of the glenoid. Results: There was significantly decreased external rotation (121.2° ± 2.8° to 113.5° ± 3.3°; P = .004), increased anteroinferior translation with an externally applied load (3.0 ± 1.2 mm to 7.5 ± 1.1 mm at 20 N; P = .008), and increased posterior (0.2 ± 0.6 mm to 2.7 ± 0.8 mm; P = .049) and inferior shift (2.9 ± 0.7 mm to 6.6 ± 1.1 mm; P = .018) of the humeral head apex in the position of maximum external rotation after soft tissue Bankart repair of a 15% glenoid defect compared with the repair of a Bankart lesion without a glenoid defect, respectively. Conclusion: Glenoid defects of 15% or more of the largest anteroposterior glenoid width should be considered the critical bone loss amount at which soft tissue repair cannot restore glenohumeral translation, restricts rotational range of motion, and leads to abnormal humeral head position. Clinical Relevance: The critical level of anterior glenoid bone loss at which bony restorations should be considered is closer to 15% of the largest anteroposterior width of glenoid for defects perpendicular to the superoinferior glenoid axis, which is lower than the commonly accepted threshold of 20% to 25%.